KETERAMPILAN ANSAMBEL DALAM MUSIK KAMAR (STUDI KASUS MARSKANSKEY STRING QUARTET) - Arum Kusuma Dewi; Royke Bobby Koapaha; Gabriel Roosmargo Lono Lastoro Simatupang (Institut Seni Indonesia Surakarta, 2022)
String Quartet is the most popular form of Chamber Music. In a string quartet there are no conductors as leaders, directors and music coordinators, no wonder many quartets end up disbanding due to problems. Marskanskey String Quartet is a group from Jogja that has been around for a long time and has more achievements, although based on initial observations this group looks the same as other groups. This research was appointed to find out what aspects of ensemble skills, how to apply ensemble skills in the Marskanskey group. To explore how the application of ensemble skills in the Marskanskey group, the author discusses the case with Keller's theory of ensemble skills. The author's theory considers that he is able to describe the discourse thoroughly, comprehensively and deeply, namely skills from the rehearsal process to performances. This research is a qualitative research with a case study approach. The results showed that Marskanskey had applied ensemble skills both in rehearsal and concert. With strategies in practice, including self-preparation until perfomances can influencing and supporting the success of a group to achieve maximum sound production. Interestingly, the researchers found a shift in function in the use of cues, as well as limitations in Keller's theory, namely the online cog-motor ensemble skill that occurs automatically.